Impact of Chatbot on Customer Loyalty in Nepalese Organization - Joshi, Bhupendra (Nepalese Journal of Business, 2024)
This study examines the impact of chatbot on customer loyalty in Nepalese organization. Customer loyalty is the dependent variable. The selected independent variables are use of chatbot, chatbot responsiveness, chatbot personalization, customer service quality, brand reputation, and customer experience. The primary sources of data is used to assess the opinions of respondents regarding use of chatbot, chatbot responsiveness, chatbot personalization, customer service quality, brand reputation, and customer experience. The study is based on primary data of 124 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of impact of chatbot on customer loyalty in Nepalese organization. The study showed that a positive impact of use of chatbot on customer loyalty. It indicates that using chatbot leads to change in customer loyalty. Similarly, chatbot responsiveness is positively correlated to customer loyalty. It indicates that better responsiveness stimulates the customer loyalty. Likewise, chatbot personalization is positively correlated to customer loyalty. It indicates that better personalization can stimulates the customer loyalty. Further, customer service quality is also positively related to the customer loyalty. It indicates that service quality leads to change in customer loyalty. Likewise, brand reputation is positively correlated to customer loyalty. It implies that good brand image leads to change in customer loyalty. In addition, customer experience is also positively correlated to the customer loyalty. It means that best experience of customer leads to change in customer loyalty.